2016
DOI: 10.1158/1538-7445.am2016-4779
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4779: In silico design, synthesis and evaluation of a new family of C1-substituted pyrrolobenzodiazepines (PBDs)

Abstract: The pyrrolobenzodiazepines (PBDs) are a class of naturally occurring and synthetic DNA minor-groove binding agents. They covalently bind to the C2-amino group of guanines, and can form mono-alkylated adducts and cross-links depending on the structure of the molecule. PBDs can be extremely cytotoxic, and there are reports of IC50 values in cell lines in the high femtomolar ranges. Synthetic A-ring-linked PBD dimers have found use as payloads in antibody drug conjugates (ADCs) due to their potent cytoxicity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[31a] Studies have also shown that replacement of the C1-atom itself with an oxygen can provide analogues (e.g., oxazolobenzodiazepines) with similar activity to the parent PBDs. [53] C1-substituted PBD monomeric conjugates have also been synthesized recently, and shown to have cytotoxicity in the nanomolar range. [54] Molecular modeling studies have shown that the C1-polyamide substituents locate in the minor groove and generate additional hydrogen bonding and other interactions, thus enhancing DNA-binding affinity and cytotoxicity.…”
Section: C-ring Substitutionmentioning
confidence: 99%
“…[31a] Studies have also shown that replacement of the C1-atom itself with an oxygen can provide analogues (e.g., oxazolobenzodiazepines) with similar activity to the parent PBDs. [53] C1-substituted PBD monomeric conjugates have also been synthesized recently, and shown to have cytotoxicity in the nanomolar range. [54] Molecular modeling studies have shown that the C1-polyamide substituents locate in the minor groove and generate additional hydrogen bonding and other interactions, thus enhancing DNA-binding affinity and cytotoxicity.…”
Section: C-ring Substitutionmentioning
confidence: 99%